Caracterização espectro-temporal do Carthamus Tinctorius L. - Sutil, Eduardo Lange (2021)
The profile that describes the spectral pattern of agricultural crops derives from spectral information acquired by remote sensing, with data collected by terrestrial sensors throughout the plant's vegetative cycle. Although there is intense research with energy crops, with safflower being one of them, the characterization of the spectral pattern of this crop is not known yet. The importance of knowing these standards makes it possible to monitor the crop more quickly, in relation to the attack of pests, diseases, water and nutritional stresses that the plant may suffer, which can lead to financial losses and a drop in production. This work aimed to determine the spectral pattern of safflower obtained by terrestrial sensors in relation to the phenological phases of the crop. The experiment was installed at the Experimental Nucleus of Agricultural Engineering - NEEA, Unioeste/Cascavel-Pr, the sowing was mechanized in an area of 900 m². For spectral characterization, a spectroradiometer called FieldSpec 4 was used and to obtain the leaf area index (LAI) the sensor LAI-2200 was used. In characterizing the spectral pattern of safflower, it was possible to observe variation in reflectance according to the phenological phases of the rosette, flowering, and maturation. Safflower yield reached an average of 895 kg.ha-1 , below its yield potential. In the analyzes carried out in general, no significant correlations were found between the vegetation indices versus the IAF and versus the Productivity (Kg.ha-1 ) of safflower, except between the modified normalized difference vegetation index (mNDVI) and the normalized difference of nitrogen Index (NDNI) that significant positive correlations were found. It is concluded that safflower showed variation in reflectance between its phenological phases and the linear regression models generated stood out in the vegetative cycle of the maturation phase, for IAF versus NDNI and Productivity versus mNDVI respectively with R² values of 0,46 and 0,39 respectively.